Wild Type TDP-43 Induces Neuro-Inflammation and Alters APP Metabolism in Lentiviral Gene Transfer Models - Herman, Alexander M. (2012)
The transactivation DNA-binding protein (TDP-43) pathology is associated with Fronto-Temporal Lobar Dementia (FTLD) with ubiquitinated inclusions and some cases of Alzheimer's disease (AD). Proteolytic fragments of β-amyloid precursor protein (βAPP) are detected in AD as well as the cerebrospinal fluid (CSF) from FTLD and Amyotrophic Lateral Sclerosis (ALS) patients, suggesting alteration in APP processing. Because of the overlap in TDP-43 pathology between FTLD and AD, we sought to determine whether there is a relationship between TDP-43 and APP metabolism. We generated gene transfer models using lentiviral delivery of human TDP-43 and Aβ(1-42) into the rat primary motor cortex and examined their role 2 weeks post-injection. Expression of TDP-43 and/or Aβ(1-42) increase pro-inflammatory markers, including Interleukin (IL)-6, tumor necrosis factor (TNF-α), glial neurofibrillary proteins (GFAP) and ionized calcium binding adaptor molecule 1 (IBA-1). Lentiviral Aβ(1-42) up-regulates endogenous TDP-43 and promotes its phosphorylation, aggregation and cleavage into 35kDa fragments. Inversely, lentiviral TDP-43 expression increases the levels and activity of β-secretase (BACE), accelerating production of APP C-terminal fragments (C99) and Aβ(1-40). Here we show that TDP-43 up-regulates APP metabolism and suggest a mechanistic link between TDP-43 and BACE.